ChemInform Abstract: Synthesis of Tetrahydro‐β‐Carbolines from Phthalic Anhydrides and Tryptamine. Issue 16 (April 2015) - Sun, Yan‐Ni; Wang, Cui‐Ling; Zhang, Ning; Wang, Zheng; Liu, Zhu‐Lan; Liu, Jian‐Li
Abstract The title compounds are obtained by a sequence of intermolecular condensation, selective reduction, and intramolecular cyclization starting from phthalic anhydrides and tryptamines.